2022
DOI: 10.3389/fmicb.2022.820484
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum 0111 Protects Against Influenza Virus by Modulating Intestinal Microbial-Mediated Immune Responses

Abstract: There are some limitations of traditional influenza vaccines concerning novel mutant strains. Therefore, it is particularly important to develop preventive means for antigen-unrelated types of influenza viruses. Recent studies have shown that probiotics can modulate the immune system and reduce the severity of viral infections. In this study, we investigated the potential of Lactiplantibacillus plantarum 0111 against influenza virus H9N2. Challenge experiments showed that L. plantarum 0111 pretreatments could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The results of several studies have revealed that the use of probiotics (mostly from the Lactobacillus and Bifidobacterium genera) is beneficial during influenza (18,(68)(69)(70)(71)(72). Some probiotics can prophylactically prime antiviral responses in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of several studies have revealed that the use of probiotics (mostly from the Lactobacillus and Bifidobacterium genera) is beneficial during influenza (18,(68)(69)(70)(71)(72). Some probiotics can prophylactically prime antiviral responses in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…The results of preclinical studies suggest that antibiotic treatment and thus functional dysbiosis of the gut microbiota enhance susceptibility to influenza (15). Conversely, shaping the intestinal microbiota with probiotics or prebiotics might be instrumental in protecting the body against severe influenza (16)(17)(18)(19). In mechanistic terms, the gut microbiota influences the lungs' defenses and controls pulmonary disease outcomes through a broad panel of microbial metabolites and membrane components (20).…”
Section: Introductionmentioning
confidence: 99%
“…Then, cell filters were inserted to collect the bacteria and centrifuged at 600×g for 10 min. The samples were then added to 10% glycerol and stored at −80 °C [ 23 ]. Prior to FMT, PBS was used instead of glycerol, and the number of viable bacteria was subsequently counted by methylene blue staining.…”
Section: Methodsmentioning
confidence: 99%
“…These microorganisms are essential for maintaining a balanced microbial environment within the body, preventing harmful bacteria from colonizing, and protecting the integrity of mucosal barriers [2]. Additionally, lactic acid bacteria at 0, 1, 2, 3,4,5,6,7,8,9,10,11,12,16,20,24, and 28 h. The growth curve was plotted with the incubation time as the horizontal coordinate and OD 600 as the vertical coordinate. The pH of the medium was measured at 0, 4,8,12,16,20,24,28,40, and 52 h. The pH curve was plotted with the incubation time as the horizontal coordinate and pH as the vertical coordinate.…”
Section: Introductionmentioning
confidence: 99%